Isolation, Synthetic Studies and Biological Activities of the Marine Triindole Alkaloids Pseudellone C, Metagenetriindole A, Araiosamine A-D and Bengacarboline - Majik, Mahesh S.; Parvatkar, Rajesh R. (Current Organic Chemistry, 2023)
The indole nucleus is one of the most important ring systems for pharmaceutical development. Various natural products of new molecular structures with diverse biological activities have been reported from marine flora and fauna, thus ensuring motivation in the search for newer natural products. The unique structural features of triindole containing three indole rings and impressive biological activities make these alkaloids an attractive target for drug discovery. This minireview highlights the significance of various strategic innovations towards these structurally unique and simplest alkaloids of marine origin (i.e., pseudellone C, metagenetriindole A, araiosamine and bengacarboline) and highlights the isolation, structure, synthesis, biosynthesis and biological activities covering literature till 2023.
Keywords: marine flora and fauna